Can the Buzz Group Strategy Unlock Potential? Exploring Its Impact on Enhancing Students’ Writing Skills Through a Quasi-Experimental Study - Prastyawan, Prastyawan; Jamilah, Jamilah (VELES Voices of English Language Education Society, 2024)
Writing is a complex skill that poses significant challenges for students in their native or foreign languages. To address these challenges, educators must adopt effective teaching strategies. This study investigates the effectiveness of the Buzz Group strategy, a promising approach to enhancing students' writing skills. Conducted at a vocational school in Tuban, this quasi-experimental research compared the writing abilities of two groups of tenth-grade students: an experimental group taught using the Buzz Group strategy and a control group receiving traditional lecture-based instruction. The study involved 61 students randomly assigned to the experimental group (X TKJ A) or the control group (X TKJ B). Pre- and post-test scores were analyzed using the Wilcoxon Signed Rank test, revealing significant improvements in the writing abilities of the Buzz Group participants. While both groups had similar baseline scores, the post-test results showed a marked improvement in the experimental group (mean score = 88.50) compared to the control group (mean score = 65.81). The p-value of 0.000 led to rejecting the null hypothesis, confirming the Buzz Group strategy's efficacy in improving writing skills. In summary, this study provides empirical evidence that the Buzz Group technique significantly enhances the writing capabilities of vocational school students. This finding supports the strategy's potential as an effective tool for writing education.